2008
DOI: 10.1002/ijc.23655
|View full text |Cite
|
Sign up to set email alerts
|

Risk of different histological types of postmenopausal breast cancer by type and regimen of menopausal hormone therapy

Abstract: In a large population-based case-control study in Germany, including 3,464 breast cancer cases aged 50-74 at diagnosis and 6,657 population based and frequency matched controls, we investigated the effects of menopausal hormone therapy (HT) by type, regimen, timing and progestagenic constituent on postmenopausal breast cancer risk overall and according to histological type. Data were collected by face-to-face interviews. Logistic and polytomous logistic regression analysis were used to estimate odds ratios (OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
144
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 147 publications
(158 citation statements)
references
References 42 publications
10
144
0
4
Order By: Relevance
“…Estrogen has favorable effects on insulin sensitivity, blood pressure and lipid metabolism, but androgenic activities of progestogens have unfavorable effects on these favorable effects of estrogen. In particular, testosterone-derived progestogens, such as levonorgestrel and norethisterone, have been reported to be associated with increase in the risk of breast cancer (82). Therefore, it is necessary to pay attention to lipid metabolism, insulin sensitivity and risk of breast cancer when using a testosterone-derived progestogen.…”
Section: Effects Of Testosterone-derived Progestogens In Womenmentioning
confidence: 99%
“…Estrogen has favorable effects on insulin sensitivity, blood pressure and lipid metabolism, but androgenic activities of progestogens have unfavorable effects on these favorable effects of estrogen. In particular, testosterone-derived progestogens, such as levonorgestrel and norethisterone, have been reported to be associated with increase in the risk of breast cancer (82). Therefore, it is necessary to pay attention to lipid metabolism, insulin sensitivity and risk of breast cancer when using a testosterone-derived progestogen.…”
Section: Effects Of Testosterone-derived Progestogens In Womenmentioning
confidence: 99%
“…More detailed information on the study population can be found elsewhere. 24 Face-to-face interviews were carried out by trained interviewers using a standardized questionnaire to collect information on sociodemographic characteristics as well as putative risk factors for breast cancer, including reproductive history, use of hormone replacement therapy (HRT), family history of breast cancer, physical activity, smoking and alcohol consumption.…”
Section: Study Populationmentioning
confidence: 99%
“…1 However, we are concerned by several shortcomings of this study. We cannot find an explanation or hypothesis, respectively, why 44.0% of randomly selected controls did not participate and a further 12.6% controls did not respond.…”
Section: Dear Sirmentioning
confidence: 91%
“…2,3 It is difficult to understand the nature of both varying and steadily decreasing absolute numbers of study women used for analyses. For example, overall there were 3,464 eligible cases for analyses (Table I) 1 , but how does this correspond to the sum of 4,359 cases (in situ disease excluded) in Figure 1 1 , reflecting absolute and relative numbers of study women with reported ever, current and past use, respectively? Likewise, the numbers of controls do not match.…”
Section: Dear Sirmentioning
confidence: 99%
See 1 more Smart Citation